2021
DOI: 10.3390/plants10081617
|View full text |Cite
|
Sign up to set email alerts
|

Paper Spray Mass Spectrometry on the Analysis of Phenolic Compounds in Rhynchelytrum repens: A Tropical Grass with Hypoglycemic Activity

Abstract: The characterization of plant compounds with pharmacological activity is a field of great relevance in research and development. As such, identification techniques with the goal of developing new drugs or even validating the bioactive properties of extracts must be explored in order to further expand the knowledge of plant extract composition. Most works in this field employ HPLC, when exploring non-structural and cell wall carbohydrates from Rhynchelytrum repens. Phenolic compounds were studied by classical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The presence of compounds such as caffeic acid ( m / z 179 [M − H] − ), catechin ( m / z 289 [M − H] − ), rutin ( m / z 609 [M − H] − ), procyanidin isomers, and flavonoids validated the antioxidant activity of the seed extract and were in accordance with previous reports [ 39 , 40 ]. Corroborating the experiments, some of the metabolites detected in the current work were already reported in the seeds and peels of avocado (vanillin, caffeic acid, ferulic acid, synaptic acid, kaempferol, catechin, quercetin-3-glucoside, quercetin-O-arabinosyl-glucoside, rutin, dimers A and B, and trimer A of procyanidin) [ 12 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of compounds such as caffeic acid ( m / z 179 [M − H] − ), catechin ( m / z 289 [M − H] − ), rutin ( m / z 609 [M − H] − ), procyanidin isomers, and flavonoids validated the antioxidant activity of the seed extract and were in accordance with previous reports [ 39 , 40 ]. Corroborating the experiments, some of the metabolites detected in the current work were already reported in the seeds and peels of avocado (vanillin, caffeic acid, ferulic acid, synaptic acid, kaempferol, catechin, quercetin-3-glucoside, quercetin-O-arabinosyl-glucoside, rutin, dimers A and B, and trimer A of procyanidin) [ 12 ].…”
Section: Resultssupporting
confidence: 91%
“…Paper spray mass spectrometry (PSMS) was applied to identify the natural products present in the ethanol extracts. This quick and efficient technique for chemical profile determination is commonly used in the clinic and in forensic research to identify specific ions through direct sample analysis [ 36 , 37 , 38 , 39 ]. This study showed no difference in the chemical profile of peel and seed samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds have become of great interest in research due to their beneficial health properties, among which is a great antioxidant capacity to delay or inhibit the oxidation of molecules inside the human body that cause stress and some diseases, such as cancer. Furthermore, phenolic compounds possess biological activities with effects such as antimicrobial, anti-inflammatory, and vasodilatory action within the body [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical profile analysis of the samples was performed using a LCQ Fleet mass spectrometer (Thermo Scientific, San Jose, CA, USA) equipped with a paper spray ionization source type. It was performed in triplicate in positive and negative ionization modes [35]. In this analysis, the chromatographic paper was cut into an equilateral triangle shape (1.5 cm) and positioned at the entrance of the mass spectrometer.…”
Section: Paper Spray Mass Spectrometry Chemical Profilementioning
confidence: 99%